A narrative inquiry into the agency of an EFL teacher in Western China - Gu, Haibo; Liang, Yulian; Wang, Qian (Frontiers in Psychology, 2022)
Despite the increasing interest in teacher agency in the field of language teacher psychology, little attention has been paid to how language teachers enact their agency in an under-resourced environment. To address the research gap, this narrative study explored how a secondary English as a foreign language teacher in Western China enacted his agency for professional development and identified its sources. The findings revealed that this teacher enacted his agency through passionate exploration of adaptive teaching and continuous investment in autonomous learning. His agency was attributed to the interplay of his past experiences, long-term goals, teaching beliefs, and the challenging working environment. Consequently, implications for teacher agency research and practice are discussed.